Muslim participation in community government the case of Barangay Magdalo, Lapaz, Iloilo City. - De Eyoy, Brian F. (2009.)
The Nature of Muslim Loacal participation: The case of Barangay Magdalo, La Paz, Iloilo" is a qualitative case study of the forms and frequency of Muslim political particiaption and the persuasions behind them in the basic political unit of the Philippines, the barangay. As part of the rich Philippine subcultures, the dynamic behind Muslims political involvement in a system perceived by some to be a christian model has been especially interesting. Steps explore and better understand this dynamics is rooted partly from the stimulating claim of the incompatibility of Islam and Democracy and the less desirable history of Muslim-Christian confrontations in the context of Philippines as well as the impetus of enhancing local governance through popular participation. And although major head ways are already on the ground, further enrichment of the subject's knowledge base is still significance. This study responds to such call for a deeper understanding. Especially important, it highlights the situation and interactions of a Muslim community lodged in a wider non-Muslim environment in relation to political participation. Apart from the description of the forms and frequency of Muslim local political participation, this study outlines important elements and factors that affect the inclination of Muslim for political involvement in the barangay and identifies the variables that discourage participation . Making use of the two initial data sets on the forms and frequency and the factors affecting participation finally, the study hopes to relate a location-wise approach on enhancing both formal and informal mechanisms for political participation on the Muslim community in Barangay Magdalo, La Paz, Iloilo. The aforementioned objectives were carried out on and investigated on the field using parameters and appropriate methodologies categorized fitting for a qualitative research. Purposive sampling was used to select the respondents for this study and a survey and key informant interview (KII) were utilized for the gathering of data. Lastly, the analysis and presentation of the results are composed partly of a descriptive statistical analysis and elaborations, explanation of meanings in text and tabular forms., in terms of political participation, the lack or absence of resources in the forms of time (most significantly), money and skills has proved to be a major constraint in the case of the Muslims in barangay Magdalo, La Paz, Iloilo. Clinging to a single representative as well denies ordinary Muslims exposure to barangay officials and government processes at the local level. Awareness however of the venues and formal forms of participation is not minimal among the Muslims. In enhancing participation, LGUs should channel their efforts through the mosque where Muslims regularly gather to attend to their religious duties.
Thesis (Undergraduate, Bachelor of Arts in Political Science ) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Muslims -- Brgy. Magdalao, Lapaz, Iloilo City